Construction Innovation of Urban Green Logistics Centers for Agricultural Products. Issue 3 (1st September 2016) - Zhou, Lingyun; Wu, Jie; Mu, Dong; Wu, Yachao; Gu, Zhonghua
Abstract : As a crucial element of city planning, an adequately planned logistics center for agricultural products can improve the circulation efficiency of agricultural products, thereby contributing to a convenient lifestyle of urban residents. First, this study analyzed the functional zones of urban green logistics centers for agricultural products based on low-carbon idea. A method was also proposed to calculate the area of each functional zone. Moreover, this study proposed a layout planning innovation method of urban green logistics centers for agricultural products based on logistics motion line analysis and logistics intensity calculation. Lastly, this study analyzed the application processes of the layout planning methodology according to the topographical conditions of Huai'an logistics center project case in China. Results of the case study show that the construction innovation method proposed in this study is scientific, reasonable, and practical. The construction innovation method can be also used for the planning and designing of similar urban logistics centers.